Efficacy of Intrauterine Perfusion of Cyclosporin A for Intractable Recurrent Spontaneous Abortion Patients With Endometrial Alloimmune Disorders: A Randomized Controlled Trial - Zhao, Long; Qi, Lijuan; Fu, Jinhua; Bi, Shuqin; Li, Lin; Fu, Yinghui (Frontiers in Physiology, 2021)
Objective To explore the therapeutic efficacy of intrauterine perfusion of cyclosporin A (CsA) in intractable recurrent spontaneous abortion (RSA) patients with endometrial alloimmune dysfunction. Methods This is a randomized controlled trial (RCT) of patients with intractable RSA with endometrial alloimmune disorders. A total of 201 women were enrolled, all of whom had at least 3 serial abortions and endometrial alloimmune dysfunction. Participants were randomly assigned to two groups. The CsA group (n =101) received intrauterine infusion of 250 mg CsA on the 3rd and 7th days after menstruation for 2 menstrual cycles, while the placebo group (n =100) received placebo. The birth of healthy, deformity-free babies was the main study outcome. Results In total, 75 (74.26%) women in the CsA group and 59 (59.00%) women in the placebo group gave birth to healthy babies [P =0.01, OR =2.01; 95% CI (1.10～3.65)]. Compared to the placebo group, the CsA group had dramatically lower endometrial CD56+ cell and CD57+ cell concentrations at the luteal phase of the second menstrual cycle (P<0.05). Conclusion Intrauterine perfusion of CsA was confirmed to be a promising approach for the treatment of intractable alloimmune RSA.